Kritik sastra Indonesia modern - Djoko Pradopo, Rachmat, 1939- (Yogyakarta : Gama Media, 2002)
Criticism on modern Indonesian literature.
Revision of the author's thesis (doctoral)--Universitas Gadjah Mada, 1989.
Includes bibliographical references (p. [465]-483).
Koleksi Sumbangan : Zainal Abidin Abdul Wahid.
Keywords: Indonesian literature -- 20th century -- History and criticism